Literacy Hub (L-hub): Studi Strategi Literasi Pemerintah Daerah (Studi Kasus di Kota Baubau) - Herie Saksono (Jurnal Kebijakan Pembangunan, 2020)
Literacy is still a problem in various regions. The times’ development has also changed the spectrum of literacy, so literacy is not just the ability to read, write, and count. The results of the measurement of various international institutions prove how the condition of literacy has deteriorated. How is the management of literacy carried out by the Government, Regional Government and the community? What should literacy stakeholders do in an effort to develop a cultural literacy? This study aims to describe the condition of literacy in the region, encourage the presence of the Government and Regional Governments to initiate extraordinary agenda of literacy implementation, and provide understanding to the public regarding the availability of public participation space to actualize literacy culture. This study used a descriptive qualitative approach to describe literacy in the area with a case study method in Baubau City. The study concluded the importance of rearranging literacy management in an integrated manner - Central and regional by involving stakeholders in literacy. It is recommended that the Baubau City Government initiate the Literacy Hub (L-Hub) which will be an accelerator of the development of cultural literacy by prioritizing the active role and collaboration between community elements. In addition, it is necessary to create a conducive climate that supports ecosystem literacy and literacy as a lifestyle for the sake of the creation of literate generations that will accelerate the realization of the city of literacy. Abstrak Literasi masih menjadi problematika di berbagai daerah. Perkembangan zaman turut merubah spektrum literasi, sehingga literasi tidak sekedar kemampuan membaca, menulis, dan berhitung. Hasil pengukuran berbagai institusi internasional membuktikan betapa terpuruknya kondisi literasi. Bagaimana pengelolaan literasi yang dilakukan Pemerintah, Pemerintah Daerah, dan masyarakat? Apa yang harus dilakukan para pemangku kepentingan literasi dalam upaya mengembangkan budaya literasi? Kajian ini bertujuan mendeskripsikan kondisi literasi di daerah, mendorong kehadiran Pemerintah dan Pemerintah Daerah untuk menginisiasi extraordinary agendapenyelenggaraan literasi, dan memberi pemahaman kepada masyarakat terkait ketersediaan ruang partisipasi publik untuk mengaktualisasikan budaya literasi. Kajian ini menggunakan pendekatan kualitatif deskriptif untuk mendeskripsikan literasi di daerah dengan metode studi kasus di Kota Baubau. Kajian menyimpulkan pentingnya menata kembali manajemen literasi secara terintegrasi - Pusat dan daerah dengan melibatkan para pemangku kepentingan literasi. Direkomendasikan agar Pemerintah Kota Baubau menginisiasi Literacy Hub(L-Hub) yang akan menjadi akselerator pengembangan budaya literasi dengan mengedepankan peran aktif dan kolaborasi antarelemen masyarakat. Selain itu, diperlukan penciptaan iklim kondusif yang mendukung ekosistem literasi dan pembiasaan berliterasi sebagai gaya hidup demi terciptanya generasi literat yang akan memercepat terwujudnya kota literasi.